An overview: effectiveness of different arrangement for electrode guard in electrical capacitance tomography - Abd Shaib, Mohd Fadzli; Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Abd Jamil, Mahadi; Leow, Pei Ling (International Frequency Sensor Association (IFSA), 2011)
Electrical capacitance tomography (ECT) system is useful to obtain information about the spatial distribution of a dielectric materials mixture inside a vessel. It has been suggested by many researchers previously to use guard electrode in ECT sensors. This paper describes various types of design for guard electrode in Electrical Capacitance Tomography (ECT) sensor. The design of these electrode guards is vital to reduce crosstalk (undesired signals) between the adjacent electrodes (positioned at the outside of the measured pipe) since the crucial signals are only inside the pipe. There are three types of electrode guards designed by various researchers which are radial guard, axial guard with end guard and driven guard. The configuration and the effectiveness of each designed electrode are discussed. Other than that this paper introduced new design of electrode guards which are embedded on electrode sensor instead of placing separately between or around adjacent measuring electrodes as the previous design.